KEPEMIMPINAN DALAM LEMBAGA PENDIDIKAN ISLAM - Colle Said (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2018)
Leadership is the process of activities of someone who has the art / ability to influence, coordinate and move individuals so that cooperation arises regularly in an effort to achieve common goals that have been established / formulated. While educational leadership, namely the process of activities influencing, moving and coordinating individuals, organizations / educational institutions to achieve certain goals that have been formulated. Leader skills operate the organization. is skill to cooperate, motivate and lead and technical skills, namely skills that must be possessed by the principal in using knowledge, methods, techniques, and equipment to complete certain tasks. Other activities that the headmaster must do as a self-developer are learning and observing daily work in the wet environment, observing management activities in a planned and creative way to develop new methods in the learning process and building networks.